THE INFLUENCE OF PRICE, PROMOTION, LOCATION, AND BRAND IMAGE ON PURCHASE DECISIONS - Dini Anggraini; Ridho Saputra; Lukmanul Hakim; Rona Tanjung; Tibrani Tibrani; Arnesih Arnesih (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
This study aims to test and analyze the influence of price, promotion, location, and brand image on purchase decision and to test and analyze the influence of price, promotion, location, and brand image simultaneously on purchase decision. The applied research type is a correlation study with quantitative methods. The population of this study was consumers of rumah makan “Warung Bude”. The research sample consisted of 50 people, taken with a accidental sampling technique. Data obtained by distributing questionnaires then analyzed using multiple linear regression and hypothesis testing using SPSS version 25. The results of this study are: (1) price partially has an influence on purchase decision, (2) promotion partially has no influence on purchase decision, (3) location partially has an influence on purchase decision, (4) brand image partially has an influence on purchase decision, (5) price, promotion, location, and brand image simultaneously have a influence on purchase decision.